(untitled) (The Research of Medical Science Review, 2024)
Background: Cholangitis is a potentially life-threatening infection of the biliary system that may occur after an endoscopic retrograde cholangiopancreatography (ERCP). Complications are related to manipulation of the bile duct during ERCP, and not surprisingly these hazards increase with pre-existing obstruction or stone disease-causing superinfection in normal flora. This study was designed to assess the frequency and Associated Factors of Cholangitis After Endoscopic Retrograde Cholangiopancreatography (ERCP)". The identification and determinants of post-ERCP cholangitis are important for prevention strategies to decrease its incidence as early recognition with adequate treatment is crucial in the reduction of mortality burden created by these factors.METHODOLOGY: This cross-sectional study was conducted in the Department of Gastroenterology, Shaheed Mohtarma Benazir Bhutto medical University Larkana from March 2024 to September 2024. A sample of 245 patients aged 18–70 years, either gender scheduled to undergo diagnostic or therapeutic ERCP, was selected using nonprobability consecutive sampling. Investigations including liver function tests were performed and preoperative ALT and AST levels were recorded. All patients underwent a thorough clinical assessment 24 after ERCP, including investigation such as liver function tests (LFTs) and blood culture. Post-operatively all the patients were monitored for post ERCP cholangitis. Patients were then divided into two groups. Group A consisted of patients diagnosed with cholangitis while Group B patients without post-ERCP cholangitis. The SPSS version 26.0 was used to analyze the data. Descriptive statistics which include mean with standard deviation and frequency with percentage were calculated. The statistical test of significance was applied at 5% level of significance. RESULTS: The mean ± SD of age was 58.73 ±7.71 years among them 55.5% were male and 44.5% were female. Patients who underwent ERCP, 72 (29.4%) developed post-procedure cholangitis. Patients with cholangitis had a significantly longer hospital stay (9.75 ± 9.00 vs. 4.25 ± 2.75 days, p = 0.0001) and higher fever occurrence post-ERCP (44.4% vs. 7.5%, p = 0.0001). Two biliary stents(23.6% vs.8.1%, p = 0.003) and tumor localization in the pancreatic head (p = 0.001), CBD (p = 0.023), or periampullary region (p = 0.0001) were significantly associated with cholangitis. CONCLUSION: These results suggest that cholangitis is a common post-ERCP complication, and its higher risk can be attributed to longer hospital stay, fever onset after surgery, receiving multiple biliary stents or the primary tumor located at pancreatic head region or periampullary space. Detection of these high-risk factors may help to identify patients who are at increased risks with better post-ERCP monitoring and early appropriate management improving patient outcomes.